2011
DOI: 10.1108/00070701111174587
|View full text |Cite
|
Sign up to set email alerts
|

Development of soy‐based cream cheese via the addition of microbial transglutaminase, soy protein isolate and maltodextrin

Abstract: Purpose -The aim of this study is to develop a soy-based cream cheese (SCC) with textural characteristics comparable to that of commercial dairy cream cheese (DCC) via the addition of microbial transglutaminase (MTG), soy protein isolate (SPI) and maltodextrin (MD). Design/methodology/approach -Response surface methodology (RSM) was employed in this study to determine the effects of MTG, MD and SPI on firmness of SCC. Findings -The second-order model generated via RSM was significant with only a 9.76 per cent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…This is due to the fact that MTGase could modify the textural properties of cheese through the formation of covalent bonds of ε-(γ-glutamyl) lysine, which were catalyzed by the enzyme [15] [41] [45]. The intra-and intermolecular crosslinks induced by this enzyme yielded a strong three-dimensional gel network thus increased the hardness of cheeses containing MTGase [53].…”
Section: Hardnessmentioning
confidence: 99%
“…This is due to the fact that MTGase could modify the textural properties of cheese through the formation of covalent bonds of ε-(γ-glutamyl) lysine, which were catalyzed by the enzyme [15] [41] [45]. The intra-and intermolecular crosslinks induced by this enzyme yielded a strong three-dimensional gel network thus increased the hardness of cheeses containing MTGase [53].…”
Section: Hardnessmentioning
confidence: 99%
“…Microbial analysis showed that the incorporation of potassium sorbate more than doubled the shelf-life of the products up to 60 days. A much firmer textured soy cream cheese was prepared by combinations of hard tofu, 5% of palm oil w/w, and 3% of NaCl w/w (Lim et al 2011). Using tofu, mozzarella, and cheddar cheese blended in ratios of 20:70:10 produced a processed cream cheese spread with a pleasing quality (Verma et al 2013).…”
Section: Recently Developed Soy Cheese Types Soy Cheese Types Based Omentioning
confidence: 99%
“…Mahdy et al (2004) reported that the use of SPI in cheddar cheese improved the sensory properties of cheese after 5 months' ripening and did not impart any bitter offflavor. It was suggested incorporating 5 g/L of soy protein concentrates into the soy cream cheese made it more acceptable in terms of flavor (Lim et al 2011). A gouda analog with soy proteins was not sour and had a good taste, due to some flavor substances such as different fatty acids, diacetyl, and acetoin produced from 0.5% sodium citrate (Amar 2012).…”
Section: Soy Cheese Types Based On Sensory Property Development Flavomentioning
confidence: 99%
“…-independent activity and stability over a wide range of pH (4.5-8.5) and temperature (Kieliszek and Misiewicz 2014;Kuraishi et al 2001). Numerous protein substrates have been identified for this enzyme including soy, whey, casein, myosin, gluten, oat globulin, peanuts (Di Pierro et al 2013;Kuraishi et al 2001;Lim et al 2011;Renzetti et al 2012;Schoenlechner et al 2013;Stangierski et al 2014). Activa EB, Activa WM, Sapronga TG1 are some of the commercially available MTG preparations.…”
Section: Food Modificationmentioning
confidence: 97%